Ts. Dr. Roshahliza invents smart solar irrigation system for areas without electricity - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2021)
A researcher from the Faculty of Electrical and Electronic Engineering Technology (FTKEE), Universiti Malaysia Pahang (UMP), Ts. Dr. Roshahliza M Ramli, 38, has invented a small-scale and portable smart solar irrigation system for use in areas without electricity.